Isolamento de Campylobacter jejuni em carcaças de frango coletadas em indústrias frigoríficas de Minas Gerais - Eronilda Castro Pena (2012)
In order to evaluate the microbiological quality of broiler carcasses produced in Minas Gerais State, by the evaluation of contamination by microorganism Campylobacter spp., were collected, by official inspection services, 246 samples of broiler carcasses, frozen and chilled, from the five regions of the Minas Gerais State. The methodology used to detection of microorganism was the ELFA technique (Enzyme Linked Fluorescent Assay) using the equipment VIDAS 30 and the confirmation was performed by biochemical tests, using the equipment VITEK 2. Only five samples (2.1%) were positive to Campylobacter spp. The low rate of positivity was probably due to the cooling and freezing conditions at which the samples were submitted, because when the microorganism Campylobacter enters injury conditions its cell morphology changes from helical to coccoidal. The coccoid form is considered viable but not culturable but can be infective. Furthermore, the ELFA method used to detect this pathogen in food has higher detection limits, which requires an enrichment stage to allow for the multiplication of the target organism.